Impacts of Salmonella enteritidis infection on liver transcriptome in broilers. Issue 5 (19th November 2012) - Coble, Derrick J.; Sandford, Erin E.; Ji, Tieming; Abernathy, Jason; Fleming, Damarius; Zhou, Huaijun; Lamont, Susan J.; Burt, David W.; Farlie, Peter G.
<x xml:space="preserve">Abstract</x> Salmonella enterica serovar enteritidis is an enteric bacterium that can contaminate chicken eggs and meat, resulting in production losses and consumer illness. To provide insight into the systemic metabolic effects of S. enteritidis infection, liver samples were harvested 10‐days postinfection from broiler hens. Hepatic global gene expression levels were assessed using a chicken 44K Agilent microarray. Forty‐four genes were differentially expressed at a significance level of q value < 0.05. One hundred eighty‐three genes were differentially expressed at a suggestive significance level of q value < 0.1. A predominance of downregulation existed among significantly differentially expressed genes. Cell cycle and metabolism networks were created from the differentially expressed genes. Mitochondria‐mediated apoptosis, electron transport, peptidase activity, vein constriction, cell differentiation, IL‐2 signaling, Jak‐Stat signaling, B‐cell receptor signaling, GDP/GTP exchange, and protein recycling were among the functions of the differentially expressed genes that were down‐regulated in response to S. enteritidis. The effects of S. enteritidis infection on the liver transcriptome profiles of broilers reflect a predominance of downregulation of genes with cell cycle and metabolic functions. The most pronounced response was the downregulation of genes that function in metabolic pathways, inflammation, and mitochondria‐mediated apoptosis. These results provide insight into important systemic metabolic mechanisms that are active in the chicken liver in response to S. enteritidis infection at 10‐days postinfection. genesis 51:357–364, 2012. © 2012 Wiley Periodicals, Inc.